Level of evidence and geographic origin of articles published in Chilean dental journals. - Javier Moraga (Universidad de Concepción., 2014)
The aim of this study is to determine the geographic origin and level of evidence (LE) of articles published in Chilean dental journals during 2012. The target population for the bibliometric study was articles published in exclusively-scientific Chilean dental journals. These variables were analyzed: journal, area, language, country, region, design, scenario, and LE. A total of 120 articles were published in four journals: International Journal of Odontostomatology (IJOS=59), Revista Clínica de Periodoncia, Implantología y Rehabilitación Oral (PIRO=28), Journal of Oral Research (JOR=18), and Revista Dental de Chile (RDC=15). From the total, 80.83% were published in Spanish and 70% had a Chilean affiliation. Most publications corresponded to areas of pathology (21) others (20) and prosthodontics (20). None of the articles was Level 1 Evidence, 6.49% was 2b, 14.29% was 2c, 63.64% was 4, and 15.58% was 5. Chilean dental journals mainly publish articles of domestic origin and low LE.